Evaluation of the causal relationship between 28 circulating biomarkers and osteoarthritis: a bidirectional Mendelian randomization study - Xiao-Wei Zhu; Xiao Zheng; Lu Wang; Jia Liu; Man Yang; Ya-Qi Liu; Yun Qian; Yuan Luo; Lei Zhang (Bone & Joint Research)
Aims: Circulating biochemistry markers are commonly used to monitor and detect disease-induced dysfunctions including osteoarthritis (OA). However, the causal nature of this relationship is nevertheless largely unknown, due to unmeasured confounding factors from observational studies. We aimed to reveal the causal relationship between 28 circulating biochemistry markers and OA pathogenesis. Methods: We conducted a comprehensive bidirectional two-sample Mendelian randomization (MR) study between 28 circulating biomarkers and six OA types, using large-scale genome-wide association study (GWAS) summary statistics data from a UK Biobank cohort (n = 450,243) and the latest OA meta-analysis (n = 826,690). We replicated the significant results of low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) in an independent large GWAS dataset obtained from the Global Lipids Genetics Consortium (GLGC) (n > 800,000). Results: Using 73 to 792 instrumental variables for biomarkers, this large MR analysis identified 11 causal associations at the Bonferroni corrected significance level of 2.98 × 10-4, involving seven biomarkers and five OA types. LDL-C (odds ratio (OR) per SD increase 0.90, 95% CI 0.86 to 0.93), apolipoprotein B (OR 0.86, 95% CI 0.82 to 0.91), TC (OR 0.90, 95% CI 0.86 to 0.94), calcium (OR 0.82, 95% CI 0.75 to 0.90), and glucose (OR 0.81, 95% CI 0.73 to 0.89) are causally associated with a reduced risk of OA, while phosphate (OR 1.18, 95% CI 1.08 to 1.30) and aspartate aminotransferase (OR 1.15, 95% CI 1.07 to 1.24) are causally associated with an increased risk. Analysis of GLGC summary statistics successfully replicated LDL-C (OR 0.93, 95% CI 0.90 to 0.96) and TC (OR 0.92, 95% CI 0.89 to 0.95). Conclusion: This comprehensive bidirectional MR analysis provides new insights into the prevention and treatment of OA, as well as understanding the biological mechanism underlying OA pathogenesis. Cite this article: Bone Joint Res 2025;14(3):259–269.